Arc-Surfaced Frictional Damper for Vibration Control in Container Crane - Gongxian Wang; Yang-Yang Wang; Jianming Yuan; Yi Yang; Dong Wang (Shock and Vibration)
In this paper, a new arc-surfaced frictional damper (AFD) is proposed and its hysteretic behavior is experimentally studied. Then the device is applied to container crane based on a seesaw mechanism. The major advantage of the seesaw damping system is that the long tension cables can be utilized as bracing between the seesaw member and the portal legs to avoid compression and buckling of the cables. A simplified trilinear force-displacement model on the basis of experimental results is adopted to represent the hysteretic behavior of AFD. After that, seismic responses of container crane with and without dampers to four earthquakes are studied using nonlinear dynamic time-history analysis. Besides this system, a diagonal-brace-AFD system is studied for comparison. A method based on the displacement and energy dissipation ratio is proposed to find the optimum slip force for seesaw damping system. Performance of AFD control system is assessed though various parameters including displacement and maximum portal frame drift angle. Results prove a feasible application of AFD control system to absorb large amounts of seismic energy and significantly reduce the structural responses.